Analisis Daya Saing Kopi Indonesia dalam Menghadapi Perdagangan Kopi Dunia - Silvi Amanda; Nia Rosiana (Forum Agribisnis, 2023)
Indonesia is the fourth largest coffee producer in the world after Brazil, Vietnam and Colombia. However, in the period 2018-2021 the value of Indonesian coffee exports decreased in line with the low volume of Indonesian coffee exports that year when compared to the previous period so that Indonesia's position fell from fourth to fifth as a coffee exporter in the world. Therefore, it is necessary to conduct research that aims to analyze the competitiveness of Indonesian coffee in the period 2011-2021 using the Revealed Comparative Advantage (RCA) analysis, Dynamic Revealed Comparative Advantage (DRCA), and Trade Specialization Index (ISP). The results showed that there was a decline in the competitiveness of Indonesian coffee in the international market, even though Indonesia is currently at the maturity stage. One of the efforts to respond to this problem is to strengthen the development of Indonesian coffee agribusiness which is integrated and collaborates with each other between its subsystems by paying special attention to coffee farmers.